Morphological and physiological responses of spring wheat (Triticum aestivum L.) to spatial arrangements - Tolmay, John Peter Cleggenett (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD(Agric) (Agronomy))--Stellenbosch University, 2008.